Learning and literacy over time : longitudinal perspectives - Sefton-Green, Julian, 1958-; Rowsell, Jennifer, 1969- (Routledge, Taylor & Francis Group, 2015)
Learning and Literacy over Time addresses two gaps in literacy research-studies offering longitudinal perspectives on learners and the trajectory of their learning lives inside and outside of school, and studies revealing how past experiences with literacy and learning inform future experiences and practices. It does so by bringing together researchers who revisited subjects of their initial research conducted over the past 10-20 years with people whom they encountered through ethnographic or classroom-based investigations and are the subjects of previous published accounts. The case studies, drawn from countries in three continents and covering a range of social worlds, offer an original and at times quite an emotive interpretation of the effects of long-term social change in the UK, the US, Australia and Canada; the claims and aspirations made by and for certain kinds of educational interventions; how research subjects reflect on and learn from the processes of being co-opted into classroom research as well as how they make sense of school experiences; some of the widespread changes in literacy practices as a result of our move into the digital era; and above all, how academic research can learn from these life stories raising a number of challenges about methodology and our claims to'know'the people we research. In many cases the process of revisiting led to important reconceptualizations of the earlier work and a sense of'seeing with new eyes'what was missed in the past. The reflections on methodology and research processes will interest postgraduate and academic researchers. The studies of change and of long-term effects are widely relevant to teacher educators and scholars in language and literacy education, educational anthropology, life history research, media and cultural studies, and sociology.